2021
DOI: 10.1016/j.heliyon.2020.e05487
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between smokeless tobacco (Gutkha) and biomarkers of oxidative stress in plasma with cardiovascular effects

Abstract: Tobacco products are widely consumed around the world in smoking and smokeless tobacco (SLT) forms. Analysis of smokeless tobacco consumption suggested that the effects of nicotine and tobacco-specific N-nitrosamines, the main ingredients of smokeless tobacco are attractive to study because its consumption often results in biochemical changes of plasma parameters and markers of oxidative stress development. Smokeless tobacco users generally consume the most commonly available SLT products like khaleja brand of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…An essential function of nitric oxide synthase is to produce peroxynitrites, which initiate lipid peroxidation (2). Furthermore, nicotine and tobaccospecific nitrosamines interfere with the antioxidant system, increase ROS levels, and contribute to cellular oxidastress (2,13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An essential function of nitric oxide synthase is to produce peroxynitrites, which initiate lipid peroxidation (2). Furthermore, nicotine and tobaccospecific nitrosamines interfere with the antioxidant system, increase ROS levels, and contribute to cellular oxidastress (2,13).…”
Section: Discussionmentioning
confidence: 99%
“…A free radical, such as H2O2 ions, hydroxyl radicals, and superoxide anions, which are chemically highly reactive, can damage the lipids in the oral mucosa by activating lipid peroxidation (10). Malondialdehyde (MDA) is a product of lipid peroxidation and a biomarker of oxidative stress (11)(12)(13), which plays an essential role in DNA damage, mutagenicity, and car-cinogenesis (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Authors has also observed that people consume smokeless tobacco are also on high risk of cardiovascular disease and in our study we also observed that deceased consume SLT are affected more to sudden death of cardiac origin as compared to smoking. [14][15][16][17][18] Atheroma and calcification is common in the coronary arteries in sudden death cases. In present study it is observed that coronary atheroma present in almost all autopsies.…”
Section: Discussionmentioning
confidence: 99%
“…These data demonstrate SLT users are at high cardiovascular risk due to nicotine-induced free radicals and oxidative damage. 7 Histopathological examination of the heart is very important tool to come to definitive opinion regarding the presence of infarction at autopsy. On gross examination the infarct is not identifiable within the first 12 hours but under the microscopic examination the area of myocardial infarction presents as a circumscribed area of ischemic, coagulative necrosis (cell death).…”
Section: Economic Burden Of Chd In Indiamentioning
confidence: 99%
“…Smoking and smokeless tobacco (ST) products are the two modes of tobacco consumption that have been assessed throughout the globe and the practice of ST is common (Shaik et al 2021; Kumar et al 2017). In total, there are 1.4 billion tobacco users aged 15 years and above worldwide, 1.07 billion smokers and 367 million smokeless tobacco users.…”
Section: Introductionmentioning
confidence: 99%